Inconsistency of Pancasila Cita (Law) for Natural Resources Management - Gatot Dwi Hendro Wibowo (International Journal of Religious and Cultural Studies, 2019)
This article aims to explain the legal study side of the existence of indications of inconsistency in the management of natural resources and the environment. The inconsistencies studied are between Pancasila as the ideal foundation and ground norm of the Indonesian nation as well as the ideals of the Indonesian nation's law, with the 1945 Constitution as a constitutional foundation as well as the rule of the game in the life of the nation and state, along with its organic laws. This article is a literature review. This article produces 3 arguments namely at the macro, micro, and socio-cultural level. On a macro scale, the spirit of "pro-environment" needs to be a mindset and attitude of policymakers, both in the executive and legislative branches, both at the national and regional levels. On the micro-scale, humans must take into account other values ​​besides technical and economic values. Socio-cultural, other values ​​in the context of natural resource management and the environment are basically the values ​​of local wisdom (local wisdom), which is the recipient of an intense interaction of the archipelago community of a plural and plural nature. Unfortunately, in some cases, precisely the value of local wisdom is often ignored in decision making.